Determination of heavy metals in freshly caught fish from the Dnipro River (Ukraine) - Kruchynenko, O.; Mykhailiutenko, S.; Klymenko, O.; Kravchenko, S. (Scientific Progress & Innovations, 2024)
Heavy metals are common micropollutants and are considered a problem worldwide. Most heavy metals are found in wastewater from factories and farms, which are usually discharged into lakes and rivers. Fish is a staple food in many regions of the world. At the same time, fish can accumulate more heavy metals in their gills, kidneys, liver, intestines and muscles than in water. In Ukraine, insufficient attention is paid to the study of the content of chemical elements in fish, in particular in muscles. Therefore, the purpose of the study was to determine the content of heavy metals in the dorsal muscles of the fish Carassius carassius (Linnaeus, 1758). Based on the results of the research, the concentration of heavy metals (Pb, Cd, Cu, As, Zn, Hg) in the muscles of freshly caught fish from the Dnipro River in the Poltava Region was determined. The research was carried out by the method of atomic absorption spectrometry on the basis of the Regional State Laboratory of Veterinary Medicine in the Poltava region. Mann-Whitney test was used for pairwise comparison of results. Differences between indicators in groups were considered significant at P < 0.05. Fish samples (n=5) caught from the Dnipro River were taken in two markets of the city of Poltava in the spring. The samples were immediately cooled, transported to the laboratory and stored at -20 °C until further analysis. The average concentrations of individual toxic elements in the muscles of crucian carp were determined. It was found that the lead content in the samples from the Central Market was 0.2±0.01, and from the "Brailky" Market was 0.3±0.01 mg/kg (P < 0.01). In the course of research, it was found that the concentration of cadmium in the muscles of fish purchased at the "Brailky" Market was probably higher (0.06±0.01) than in the CM 0.04±0.01 mg/kg (P < 0.01). The level of Cu, Zn, As and Hg in the dorsal muscles of freshly caught fish from the two locations was not statistically significant. In our research, the ranking series according to the level of heavy metals is presented as follows: Zn>Cu>Pb>As>Hg>Cd. The studied samples of fish entering the Central Market and the " Brailky " Market of Poltava were safe in terms of the content of heavy metals, since no sample exceeded the maximum permissible concentration level.